REDUCTION OF REAL POWER LOSS AND VOLTAGE STABILITY ENHANCEMENT BY SALMO SALAR ALGORITHM - Dr. K. Lenin (Zenodo, 2017)
This paper presents a new Salmo Salar (SS) algorithm for Solving Optimal Reactive Power Dispatch Problem. Salmo Salar Algorithm imitates the annual natural events happening in the North America. Millions of Salmo salar move about through mountain streams for spawning. Proposed SS algorithm utilizes the behaviour of Salmo Salar to solve the optimal reactive power problem. Proposed (SS) algorithm has been tested in standard IEEE 30 bus test system and simulation results shows clearly about the good performance of the proposed algorithm in reducing the real power loss and enhancing the voltage stability